Studi Eksperimental dan Pemodelan Matematika Proses Pengeringan Kakao Dengan Energi Surya Secara Intermitten - Putra, Haznam; Napitupulu, Farrel H; Ambarita, Himsar; Dina, Sari Farah (Institution for Industrial Research and Standardization of Industry - Padang, 2014)
In this research, the behaviors of cocoa drying using solar dryers have been studied. Cocoa was taken from plantation area around North Sumatra - Indonesia. Solar energy is used as a source of energy that save and clean for drying. Cocoa is a mainstay in Indonesian commodities, but quality of the current generated is relatively low. The aims of this research to gain the quality with mathematical modelling of drying by producing a good quality of cocoa. Preparation phase started from cocoa fermentation process. With some testing times, it was taken one test where the results of fermented cocoa that had been washed and dried from water content 55.83% to 7.01%, which lasted for three days, 22 to 24 April 2013 from at 7:00 to 17:00 pm (intermittent). The study was conducted at the Solar Energy Laboratory, Faculty of Engineering Department of Mechanical Engineering of North Sumatra University Medan. It is located in Medan city with the position of 3.36 Â° N - 98.4 Â° E, altitude 200 meters above sea level and meridian time (GMT +7). From the experimental results obtained an experimental equation mathematical model for intermittent drying of cocoa, with the value of diffusivity coefficient was between 1.39 x10-10 to 1.85 x10-10 m2/sec, besides the quality of the dried cocoa in this study was better in colour and not moldy than dried cacao directly under the sun.Â ABSTRAK Pada penelitian ini, perilaku pengeringan menggunakan pengering kakao tenaga surya telah dilakukan. Kakao diambil dari perkebunan di sekitar daerah Sumatera Utara â Indonesia. Energi surya digunakan sebagai sumber energi pengeringan yang hemat dan bersih. Kakao merupakan komoditi andalan di Indonesia hanya saja mutu yang saat ini dihasilkan masih terbilang rendah. Penelitian ini bertujuan mendapatkan persamaan pengeringan dengan pemodelan matematika untuk menghasilkan mutu kakao yang baik. Tahap preparasi dimulai dari proses fermentasi kakao. Dengan beberapa kali pengujian kakao, diambil hasil salah satu pengujian dimana hasil fermentasi kakao yang telah dicuci kemudian dikeringkan dari kadar air 55,83% menjadi 7,01% yang berlangsung selama tiga hari yakni 22â24 April 2013 dari pukul 07.00 â 17.00 WIB (Intermitten).Â Penelitian dilakukan di Laboratorium Solar Energi Jurusan Teknik Mesin Fakultas Teknik Universitas Sumatera Utara Medan yang berada di kota Medan dengan posisi 3.36 Â°LU â 98.4 Â°BT, ketinggian di atas permukaan laut 200 meter dan waktu meridian (7 + GMT). Dari hasil percobaan percobaan didapat persamaan model matematika untuk pengeringan kakao secara intermitten, dengan nilai koefisien difusifitas berada pada nilai 1,39 x10-10 â 1,85 x10-10 m2/detik, selain itu kualitas kakao yang dikeringkan lebih baik dari segi warna dan tidak berjamur dibandingkan dengan kakao yang dikeringkan secara langsung dibawah sinar matahari.